2009
DOI: 10.1007/bf03325113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender and school level on disordered eating behaviours and attitudes in Mexican adolescents

Abstract: The aim of this study was to assess eating behaviours and attitudes in a community sample of 615 adolescent Mexican students recruited at a middle school (192 boys and 226 girls; mean age +/- standard deviation 13.56+/-0.09) and high school (90 boys and 107 girls; mean age 16.04+/-0.12 years), who completed the Eating Attitudes Test (EAT), the Bulimia Test (BULIT) and the Body Shape Questionnaire (BSQ). Multiple analysis of variance revealed the significant effect of gender on the negative feelings, body dissa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Girls scored significantly higher than boys in the BSQ, as was also found by Conti et al (2009) and Mancilla-Díaz et al (2009). Although body image concerns have been increasing in males in the last decades (McCabe and Ricciardelli, 2004), females, especially at this age, still are thought to be more worried about their physical appearance (Penelo et al, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…Girls scored significantly higher than boys in the BSQ, as was also found by Conti et al (2009) and Mancilla-Díaz et al (2009). Although body image concerns have been increasing in males in the last decades (McCabe and Ricciardelli, 2004), females, especially at this age, still are thought to be more worried about their physical appearance (Penelo et al, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, some studies focused on gender differences for depression. It was reported that females have a higher prevalence of depression than males and of somatic symptoms such as eating disorders, poor body image, headaches, insomnia, and fatigue (Bjornelv, Nordahl, & Holmen, ; Mancilla‐Diaz et al, ; Sund, Larsson, & Wichstrom, ). All of these somatic symptoms were more strongly related to depression among females than among males (Bjornelv et al, ; Rhee, ).…”
mentioning
confidence: 99%
“…Asimismo, estudios realizados en diferentes estados de la República Mexicana han encontrado que jóvenes de la Ciudad de México y su zona metropolitana (Álvarez et al, 2003;Mancilla-Díaz et al, 2009;Unikel-Santoncini, Bojórquez-Chapela, Villatoro-Velázquez, Fleiz-Bautista y Medina-Mora, 2006;Unikel, Saucedo-Molina, Villatoro y Fleiz, 2002;Unikel et al, 2000;Vázquez et al, 2005) y de los estados de Aguascalientes (Martínez, Álvarez, Góngora, Franco y Mancilla, 2009); Guanajuato (Chávez, Macías, Gutiérrez, Martínez y Ojeda, 2004); Hidalgo (Saucedo-Molina, Escamilla-Talón, Portillo-Noriega, Peña-Irecta y Calderón-Ramos, 2008; Saucedo-Molina y Unikel, 2010), Jalisco ; Nuño-Gutiérrez, Celis-De la Rosa y ), Michoacán (Bojórquez y Unikel, 2004), Nuevo León (Alvarez et al, 2003 y Querétaro (Aguilera y Milián, 2006) presentan conductas alimentarias que suponen un riesgo para el desarrollo de TCA (e.g. dieta, atracón, consumo de producto para adelgazar, ejercicio para quemar calorías, vómito, uso de laxantes).…”
Section: Introductionunclassified